9‐Oxo‐10(E), 12(Z), 15(Z)‐Octadecatrienoic Acid Activates Peroxisome Proliferator‐Activated Receptor α in Hepatocytes. Issue 11 (19th September 2015) - Takahashi, Haruya; Kamakari, Kosuke; Goto, Tsuyoshi; Hara, Hideyuki; Mohri, Shinsuke; Suzuki, Hideyuki; Shibata, Daisuke; Nakata, Rieko; Inoue, Hiroyasu; Takahashi, Nobuyuki; Kawada, Teruo
Abstract: The peroxisome proliferator‐activated receptor (PPAR)α is mainly expressed in the liver and plays an important role in the regulation of lipid metabolism. It has been reported that PPARα activation enhances fatty acid oxidation and reduces fat storage. Therefore, PPARα agonists are used to treat dyslipidemia. In the present study, we found that 9‐oxo‐10( E ), 12( Z ), 15( Z )‐octadecatrienoic acid (9‐oxo‐OTA), which is a α‐linolenic acid (ALA) derivative, is present in tomato ( Solanum lycopersicum ) extract. We showed that 9‐oxo‐OTA activated PPARα and induced the mRNA expression of PPARα target genes in murine primary hepatocytes. These effects promoted fatty acid uptake and the secretion of β‐hydroxybutyrate, which is one of the endogenous ketone bodies. We also demonstrated that these effects of 9‐oxo‐OTA were not observed in PPARα‐knockout (KO) primary hepatocytes. To our knowledge, this is the first study to report that 9‐oxo‐OTA promotes fatty acid metabolism via PPARα activation and discuss its potential as a valuable food‐derived compound for use in the management of dyslipidemia.